Training of Learning Model Snowball Throwing of Teachers at State Elementary School - Golda Novatrasio Sauduran; Rani Farida Sinaga (Yayasan Payungi Smart Madani, 2021)
One of the presentations of teaching materials that includes aspects before being and after learning by the teacher which is used directly or indirectly in the teaching and learning process is the snowball throwing learning model. The snowball throwing model is designed like a ball game with the aim of provoking creativity in making questions as well as testing the absorption of the material that has been delivered. The implementation of this community service activity aims to improve the insight and skills of teachers in choosing appropriate learning models during face-to-face learning activities. Partners involved in this community service activity are teachers at State Elementary School No. 173553 Simaremarejae Laguboti-Tobasa , where the activity carried out was training in making questions using the snowball throwing learning model. The results of the training carried out for two days showed that the teachers at State Elementary School No. 173553 Simaremarejae Laguboti-Tobasa is enthusiastic about the material presented and already understands and is able to make practice questions using the snowball throwing learning model.